Antihumanist narratives: Greed and Source Code. - BISHOP, RYAN; CUBITT, SEAN (Screen)
The article explores specific, rare, antihumanist narrative possibilities in Hollywood cinema signified by two films Erich von Stroheim's "Greed" and Duncan Jones's "Source Code." Topics discussed include capacity for a political aesthetics predicated on antihumanist representation, intellectual, technological and cultural conditions of possibility for the salience of such representational interventions and naturalism in the motion pictures.